The Digitizing Archives as an Effort to Protect Family Archives in Tanjung Bintang Village, South Lampung, Lampung - Rinaldo Adi Pratama; Dimas Aditia; Adelia Tamara; Siti Nur Hasanah; Nur Afifah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
Family archives are records of information about the whereabouts and roles of individual family members in relation to society. This archiving activity has occurred since a person is born in this world. Like when a person is born, there will be a birth certificate filing, and one day when a person grows up and enters the world of education, an educational archive will be created and so on. Departing from the importance of the value of family archives, it is necessary to protect it. The approach used in this activity is to use a qualitative descriptive method. This is so that the data obtained can be used to draw conclusions on the problem that is the focus of research. The analysis used is individuals, namely residents of Tanjung Bintang Village. This study resulted in several findings in the form of important lessons that can be used as examples for other regions. Some of these lessons are the first; archive management awareness needs to be built early on; second; it is necessary to have the participation of the regional archives and library services in an effort to socialize archive management awareness; third; limited public information literacy greatly hinders understanding of the urgency of archive management; fourth; archive storage media is still very limited. So that the role of KKN in the History Education Program at the University of Lampung from April to June in Tanjung Bintang Village, South Lampung Regency, Lampung is very useful.